ETHICS IN HUMAN RELATIONSHIPS AND DOMESTIC VIOLENCE AGAINST MEN IN NIGERIA: AN UNSPOKEN TRUTH - Sotonye Big-Alabo; Morrison Itelimo (Universitas PGRI Madiun, 2022)
In Nigeria, domestic violence against men is uncommon. Aside from providing security and emotional support, a family should provide the safest environment for a child to grow. Domestic violence, on the other hand, is prevalent in Nigerian families and societies. Domestic violence was previously thought to be perpetrated by men against women, and that men were not victims of domestic violence in any way. According to recent studies, domestic violence against men in Nigeria is no longer a rarity, but rather a reality with varying degrees of consequences for individuals and society as a whole. It is against this backdrop that the researcher investigates the silent problem of domestic violence against men in Nigeria, the unspoken truth about gender-based violence. The purpose of this article is to examine the various sources of domestic violence against men and the importance of ethics in human relationships. The qualitative analysis method was used in this study to reveal the existence of domestic violence against men in Nigeria. As a result, the research relied on secondary sources such as journals, text, and internet sources. The concept of violence and domestic violence were examined, as well as domestic violence against men in Nigeria and the discrimination of victims. Hence, the study recommends, amongst others, that professionals such as social workers, psychologists, and counsellors should be included among the court officials who assist the magistrate in elaborating on the type of abuse the victims may be experiencing